KINERJA KELOMPOKTANI PADI DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Hardika Hardika; Rosnita Rosnita; Kausar Kausar (Indonesian Journal of Agricultural Economics, 2017)
The purposes of the research were: 1) identify the implementation of agriculture extention in the pangean district kuantan singingi, 2) analyze performance of rice farmer groups in the pangean district kuantan singingi. This research used survey method. This research was conducted in the pangean district kuantan singingi from May to October 2016. The respondents were 78 people which were selected by purposive sampling. Analysis of the data used is descriptive analysis and likert scale. The results showed that: The results showed that: 1) the implementation of counseling in the District of Pangean was carried out well, the extension workers totaling eight people assist 17 villages and this sub-district is still lacking 9 extension workers. The targets of extension activities are farmers and rice farming groups in Pangean District. Methods and materials adapted to their needs. The counseling material provided were the "jajar legowo" planting system, the benefits of using superior seeds, fertilization, administrative control and time adjustments in the planting season and extension was carried out twice a month and 2) performance of rice farmer groups in the pangean district categorized as not too good with a value score of 2.36. The ability to the plan activities of rice farmer groups have a quite good category with a value score of 2.66, the ability to organize activities categorized quite good with a value score of 2,75, the ability to implement activities categorized poor with a score of 2.11, the ability to control and report categorized as not too good with score of 2.15, and ability to develop leadership categorized as not too good with score of 2.14.